The Effectiveness Of Water-Filled Rubber Weir Management On Flood Mitigation Caused By Rain And “Rob” (Java Slang) In Demak District - Fatchur Roehman (International Conference on Coastal and Delta Areas, 2017)
In Indonesia, there are many sources of water. They can be ground water, rivers or seas which are certainly not easy to process these resources. Many problems have to be solved in processing these resources, such as flooding and